2016
DOI: 10.1007/s00330-016-4632-8
|View full text |Cite
|
Sign up to set email alerts
|

CT evaluation after neoadjuvant FOLFIRINOX chemotherapy for borderline and locally advanced pancreatic adenocarcinoma

Abstract: • Significant tumour size decreases were observed on CT after FOLFIRINOX (± chemoradiotherapy). • CT is not able to predict R0 resection accurately after FOLFIRINOX (± chemoradiotherapy). • CT is not able to predict complete response accurately after FOLFIRINOX (± chemoradiotherapy). • Even with a stable NCCN classification, BR/LA pancreatic adenocarcinoma could have R0 resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
81
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(85 citation statements)
references
References 22 publications
4
81
0
Order By: Relevance
“…The search yielded 649 studies of which 15 published between 2009 and 2017 were included in the final analysis (Fig. ) . These 15 studies included 995 patients with BRPC ( n = 683) and locally advanced ( n = 312) PDAC.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The search yielded 649 studies of which 15 published between 2009 and 2017 were included in the final analysis (Fig. ) . These 15 studies included 995 patients with BRPC ( n = 683) and locally advanced ( n = 312) PDAC.…”
Section: Resultsmentioning
confidence: 99%
“…These 15 studies included 995 patients with BRPC ( n = 683) and locally advanced ( n = 312) PDAC. All the studies originated from single institutions in the USA ( n = 9), France ( n = 3), Korea ( n = 2) and Spain ( n = 1) . Only one study was prospective in design, with the rest being retrospective (cohort or case controlled) studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Focusing on 40 BR or LAPC PDAC preoperatively treated with FOLFIRINOX, a 2015 study concluded that after preoperative therapy images no longer predict unresectability, as 70% of them were re-classified as BR or LAPC after therapy although an R0 resection was achieved in 92% of them (35). Similar results were achieved in another multicenter retrospective study with 36 patients treated with FOLFIRINOX, where despite a significant tumor shrinkage after therapy, preoperative CT failed to accurately predict resectability (36).…”
Section: Radiographic Responsementioning
confidence: 86%
“…This issue is of particular importance with modern chemotherapy, whereby more patients with borderline resectable or unresectable locally advanced PDAC are now potential candidates for resection after preoperative chemotherapy or radiotherapy. In addition, the assessment of tumour extension around the mesenteric vessels becomes difficult and inaccurate after preoperative therapy, and Hackert and co‐workers recommended evaluation by intraoperative frozen sectioning at the sites around critical arteries to determine resectability before committing to morbid radical resection.…”
Section: Discussionmentioning
confidence: 99%